THE USE OF METAPHOR IN BARACK OBAMAâS INAUGURATION SPEECH - Risdianto, Faizal (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2016)
This study is aimed to elaborate the uniqueness of Barack Obamaâs inaugural speech when he has been sworn in as the 44th US president at 20 January 2009. This research is a (qualitative) bibliographical study. The object of the study is the analysis of the use of metaphor in Barrack Obamaâs speech. There are 23 sentences chosen to represent all the metaphorical sentences of Obamaâs speech being the object of the study. Having analyzed the data by the perspective of George Lakoff and Johnsonâs conceptual metaphor, the researcher can draw a conclusion that Obama has effectively and creatively used metaphorical expressions in convincing his people about his future plans. His remarkable speech discussing how to solve the great scale of the economic mess that now confronts the US and the common feeling of the loss of national self-confidence.